The Spectrum of Fundus Autofluorescence Findings in Birdshot Chorioretinopathy. (27th January 2010) - Giuliari, GianPaolo; Hinkle, David M.; Foster, C. Stephen
Abstract : Objective . To describe the diverse patterns observed with the use of autofluorescence fundus photography (FAF) in patients with Birdshot chorioretinopathy (BSCR). Methods . A chart review of patients with BSCR seen at the Massachusetts Eye Research and Surgery Institution, who had autofluorescence fundus photography. The data obtained included age, gender, presence of the HLA-A29 haplotype, and current treatment. Results . Eighteen eyes with HLA-A29 associated BSCR were included. Four eyes presented with active inflammation. Correspondence of the lesions noted in the colour fundus photograph was observed in 3 eyes which were more easily identified with the FAF. Fifteen eyes had fundus lesions more numerous and evident in the FAF than in the colour fundus photograph. Conclusion . Because FAF testing provides valuable insight into the metabolic state of the PR/RPE-complex, it may serve as a useful noninvasive assessment tool in patients with posterior uveitis in which the outer retina-RPE-choriocapillaries-complex is involved.